Peran Guru Dalam Penanaman Pendidikan Karakter pada Anak Berkebutuhan Khusus (ABK) di SLB Negeri 1 Kota Bima - Risma, Risma; Nurhasanah, Nurhasanah; Arifuddin, Arifuddin; Irfan, Irfan; Hartati, Hartati; Nurbayan, ST. (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2024)
Education is obliged to provide equality to students without distinguishing between students' backgrounds or shortcomings, so this research aims to describe the role of teachers in instilling character in ABK and describe teachers' obstacles in carrying out learning for ABK students. This research is a qualitative descriptive study with a research approach, data collection techniques namely interviews, observation and documentation, research informants are class teachers and special assistant teachers for ABK, which were determined using purposive sampling. Data analysis uses data display, data verification and data validity testing and conclusions. The results of the research illustrate that the results of this research show that (1) cultivating student character refers to the Education Department curriculum, making a learning implementation plan for children with special needs, namely designing and implementing learning materials for children with special needs, determining learning methods, inviting cooperation, managing time according to needs. For Children with Special Needs. Meanwhile, the obstacles faced by teachers in teaching children with special needs (ABK), namely teachers have difficulty in making learning implementation plans (RPP), limitations in understanding the character of ABK, lack of special tools and equipment for ABK, limited time given by schools, because dealing with ABK requires a lot of time. many approach them emotionally, the uncertain situation and condition of ABK makes it difficult for teachers to choose methods, difficulty in getting ABK to work together during the learning process, because the child's attitude is difficult to understand.